What Makes Brand Social Media Posts Engaging? An Integrative Framework and Future Research Agenda. Issue 1 (2nd January 2023) - Deng, Qi; Hine, Michael J.; Ji, Shaobo; Wang, Yun
Abstract: Creating engaging brand posts is both vital and challenging for social media marketers. While previous research suggests that digital marketers can strategically design brand posts to enhance consumer engagement, it is unclear what post contents work better, for which brand, and in what way. Through the in-depth review of 82 empirical papers on consumer engagement with brand social media posts, this paper shows that previous research has adopted a highly consistent and convergent research design but produced many inconsistent, sometimes even contradictory results. An integrative framework of consumer engagement of brand posts on social media is developed, and four future research agendas are identified and discussed. This paper provides a landscape description on consumer engagement with brand posts on social media research and a roadmap of potential research agendas that can be further explored. This paper also provides digital marketing practitioners useful insights in designing brand posts on social media.